Analysis of Frequency and Voltage Stabilization Control in Low-Inertia Power Systems Using a Boost Converter - Renaldo Hotmartua Sinaga; Solly Aryza; Rahmaniar, Rahmaniar (INFOKUM, 2025)
Low-inertia power systems, especially those based on renewable energy sources such as solar and wind, face major challenges in maintaining frequency and voltage stability. The absence of mechanical inertia in these systems, which is usually available in synchronous generators, makes the system more vulnerable to load changes or network disturbances. Therefore, an effective control method is needed to maintain such stability. This study analysed the frequency and voltage stability control of low-inertia power systems using a Boost Converter. A Boost Converter is used to regulate and stabilize the output voltage of a fluctuating power source, such as a solar panel, by increasing the unstable input voltage. Meanwhile, a frequency control method such as is implemented to imitate mechanical inertia, thus maintaining the frequency at a desired value. The results show that the use of a Boost Converter effectively improves voltage stability, while a VSG-based frequency control strategy successfully imitates the inertia response of a synchronous generator, maintaining a stable frequency despite the system having low inertia. Thus, the combination of these two methods can improve the reliability of low-inertia power systems, especially in applications utilizing renewable energy sources.